Impact of COVID-19 on Hematology-Oncology Fellowship Programs: A Quantitative and Qualitative Survey Assessment of Fellowship Program Directors. Issue 4 (11th April 2022) - Velazquez, Ana I.; Durani, Urshila; Weeks, Lachelle D.; Major, Ajay; Reynolds, Robby; Kumbamu, Ashok; Das, Devika G.; Murphy, Martina C.; Henry, Elizabeth; Lee, Alfred I.; Marshall, Ariela L.
Abstract : PURPOSE: The COVID-19 pandemic led to unprecedented challenges in medical training, and we sought to assess the specific impact of COVID-19 on hematology-oncology (HO) fellowship programs. METHODS: We conducted a cross-sectional anonymous online survey of 103 HO program directors (PDs) in conjunction with the American Society of Hematology (ASH) and ASCO. We sought to assess the specific impact of COVID-19 on HO fellowship programs' clinical, educational, and research activities, evaluate perceptions regarding PD and trainee emotional and mental health, and identify ways to support programs. Data were analyzed using descriptive statistics, parametric and nonparametric tests, and multivariable logistic regression models. Responses to open-ended questions were analyzed with thematic analysis. RESULTS: Significant changes to fellowship activities included transitioning fellow training from outpatient clinics to telehealth (77.7%), shifting to virtual education (94.2%), and moving to remote research work (63.1%). A minority (21.4%) of PDs reported that their fellows were redeployed to cover non-HO services. Most PDs (54.4%) believed COVID-19 had a slight negative impact on fellowship training. PD self-reported burnout increased significantly from 15.5% prepandemic to 44.7% during the pandemic, and most PDs witnessed minor signs of fellow burnout (52.4%). Common PD concerns included inadequate supervision for telehealth activities, reduced opportunities for fellow advancement and promotion, lack of professional development activities, limited research operations and funding, program financial constraints, and virtual recruitment. CONCLUSION: We encourage institutions and national societies to allocate resources and develop programs that can support fellowships and mitigate the potential negative effects of COVID-19 on trainee and PD career development. Abstract :